«I hear a voice from a beauteous far away»: the phenomenon of Ovidian Renaissance in Western European culture - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The phenomenon of the Ovidian revival in the medieval culture of Western Europe is examined, its place among the minor renaissances of the Middle Ages is revealed, its significance is assessed in the context of transformations of the medieval picture of the world and its influence on the interpretation of love in the culture of the Middle Ages.